Changes in femoral trochlear morphology following surgical correction of recurrent patellar dislocation associated with trochlear dysplasia in children. (June 2018) - Fu, K.; Duan, G.; Liu, C.; Niu, J.; Wang, F.
Abstract : Aims: The aim of this study was to investigate the changes in femoral trochlear morphology following surgical correction of recurrent patellar dislocation associated with trochlear dysplasia in children. Patients and Methods: A total of 23 patients with a mean age of 9.6 years (7 to 11) were included All had bilateral recurrent patellar dislocation associated with femoral trochlear dysplasia. The knee with traumatic dislocation at the time of presentation or that had dislocated most frequently was treated with medial patellar retinacular plasty (Group S). The contralateral knee served as a control and was treated conservatively (Group C). All patients were treated between October 2008 and August 2013. The mean follow-up was 48.7 months (43 to 56). Axial CT scans were undertaken in all patients to assess the trochlear morphological characteristics on a particular axial image which was established at the point with the greatest epicondylar width based on measurements preoperatively and at the final follow-up. Results: Preoperatively, there were no statistically significant differences between the trochlear morphology in the two groups (sulcus angle, p 0.852; trochlear groove depth, p 0.885; lateral trochlear inclination, p 0.676; lateral-to-medial facet ratio, p 0.468; lateral condylar height, p 0.899; medial condylar height, p 0.816). Many radiological parameters of trochlear morphology were significantly different between the two groups at the final follow-up, including well-known parameters, such as the mean sulcus angle (Group S, 146.27° (sd 7.18); Group C, 160.61° (sd 9.29); p < 0.001), the mean trochlear groove depth (Group S, 6.25 mm (sd 0.41); Group C, 3.48 mm (sd 0.65); p < 0.001) and the mean lateral trochlear inclination (Group S, 20.99° (sd 3.87); Group C, 12.18° (sd 1.85); p < 0.001). Lesser known parameters such as the ratio of the lateral to medial trochlear length (Group S, 1.46 (sd 0.19); Group C, 2.14 (sd 0.42); p < 0.001), which is a measurement of facet asymmetry, and the lateral and medial condylar height were also significantly different between the two groups (p < 0.001). Conclusion: The femoral trochlear morphology can be improved by early (before epiphyseal closure) surgical correction in children with recurrent patellar dislocation associated with femoral trochlear dysplasia. Cite this article: Bone Joint J 2018;100-B:811–21.